Conditional inactivation of replication proteins in fission yeast using hormone-binding domains - Pai, C; Schnick, J; MacNeill, SA; Kearsey, SE (2012)
The fission yeast Schizosaccharomyces pombe is a useful model for analysing DNA replication as genetic methods to allow conditional inactivation of relevant proteins can provide important information about S-phase execution. A number of strategies are available to allow regulation of protein level or activity but there are disadvantages specific to each method and this may have limitations for particular proteins or experiments. We have investigated the utility of the inducible hormone-binding domain (HBD) system, which has been described in other organisms but little used in fission yeast, for the creation of conditional-lethal replication mutants. In this method, proteins are tagged with HBD and can be regulated with β-estradiol. In this article, we describe the application of this method in fission yeast, specifically with regard to analysis of the function of GINS, an essential component of the eukaryotic replicative helicase, the CMG complex. © 2012 Elsevier Inc.